2020
DOI: 10.1101/2020.02.25.965590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteriophages targetingAcinetobacter baumanniicapsule induce antimicrobial resensitization

Abstract: 21Carbapenem-resistant Acinetobacter baumannii is responsible for frequent, hard-to-treat and often fatal 22 healthcare-associated infections. Phage therapy, the use of viruses that infect and kill bacteria, is an approach 23 gaining significant clinical interest to combat antibiotic-resistant infections. However, a major limitation is that 24 bacteria can develop resistance against phages. Here, we isolated phages with activity against a panel of A.25 baumannii strains and focused on clinical isolates AB900 a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…In particular, identification of phages that differ in their receptor use or against which cross-resistance is unlikely to evolve would allow for better design of such therapies [ 23 , 37 , 242 ]. Moreover, identifying phages that select for resistance that have interrelated phenotypic consequences with, for example, antibiotic sensitivity is a recent advancement in the field that could directly benefit from these screening approaches [ 33 , 53 , 97 , 243 ]. By combining fitness datasets for phages and antibiotics or phage-antibiotic combination therapies [ 244 – 246 ], such screens could provide an avenue for performing high-throughput search for genetic trade-offs or “evolutionary traps” [ 33 , 53 , 97 , 243 ] that could provide a much-needed solution to overcome the antibiotic-resistance pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, identification of phages that differ in their receptor use or against which cross-resistance is unlikely to evolve would allow for better design of such therapies [ 23 , 37 , 242 ]. Moreover, identifying phages that select for resistance that have interrelated phenotypic consequences with, for example, antibiotic sensitivity is a recent advancement in the field that could directly benefit from these screening approaches [ 33 , 53 , 97 , 243 ]. By combining fitness datasets for phages and antibiotics or phage-antibiotic combination therapies [ 244 – 246 ], such screens could provide an avenue for performing high-throughput search for genetic trade-offs or “evolutionary traps” [ 33 , 53 , 97 , 243 ] that could provide a much-needed solution to overcome the antibiotic-resistance pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Despite nearly a century of pioneering molecular work, the mechanistic insights into phage specificity for a given host, infection pathways, and the breadth of bacterial responses to different phages have largely focused on a handful of individual bacterium-phage systems [9][10][11][12][13]. Bacterial sensitivity/resistance to phages is typically characterized using phenotypic methods such as crossinfection patterns against a panel of phages [14][15][16][17][18][19][20][21][22][23][24][25][26][27] or by whole-genome sequencing of phageresistant mutants [28][29][30][31][32][33]. As such, our understanding of bacterial resistance mechanisms against phages remains limited, and the field is therefore in need of improved methods to characterize phage-host interactions, determine the generality and diversity of phage resistance mechanisms in nature, and identify the degree of specificity for each bacterial resistance mechanism across diverse phage types [13,25,26,[34][35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they found that these mutants showed a decrease in biofilm formation antibiotic resistance. This study suggested that these bacteriophages cannot be used for their lytic activity only but the combination between understanding of phage receptors and bacterial resistance mechanism provides the best knowledge of the potential synergy effect of both phage and antimicrobial agents [ 91 , 114 ]. Therefore, future attention should be focused on bacteriophage therapy especially for A. baumannii with MDR resistance, which causes many epidemics in hospitals.…”
Section: The Antibiotic Resistance In a Baumanniimentioning
confidence: 99%
“…While bacteriophage-based therapies hold immense potential as biological control agents; the emergence of bacteriophage resistance mediated via: (1) receptor adaptations (mutations of phenotypical alteration resulting in decreased bacteriophage adsorption); (2) host defence systems (molecular pathways preventing or suppressing phage infections); and (3) phage-derived defence systems (molecular pathways facilitating bacterial competition of host), remains a major obstacle, hampering the effective application of this treatment ( Figure 4 ) (extensively reviewed by Egido et al [ 98 ]). The underlying resistance mechanisms have subsequently been identified and exploited in an approach referred to as “bacteriophage steering”, which involves the “exploitation-specific fitness trade-offs” associated with bacteriophage resistance, including antimicrobial re-sensitisation, reduced virulence, and colonisation defects [ 106 , 107 ]. For example, Altamirano et al [ 106 ] isolated a Myoviridae bacteriophage (ɸFG02) and an Ackermannviridae bacteriophage (ɸCO01).…”
Section: Biological Control Strategies For Mdr Xdr and Pdr ...mentioning
confidence: 99%
“…The underlying resistance mechanisms have subsequently been identified and exploited in an approach referred to as “bacteriophage steering”, which involves the “exploitation-specific fitness trade-offs” associated with bacteriophage resistance, including antimicrobial re-sensitisation, reduced virulence, and colonisation defects [ 106 , 107 ]. For example, Altamirano et al [ 106 ] isolated a Myoviridae bacteriophage (ɸFG02) and an Ackermannviridae bacteriophage (ɸCO01). Following co-culturing with the respective A. baumannii host strains, bacteriophage resistance was observed, which correlated with the loss of the CPS.…”
Section: Biological Control Strategies For Mdr Xdr and Pdr ...mentioning
confidence: 99%